Would There Be One Standard English as the Global Language? - Ienneke Indra Dewi (Humaniora, 2010)
Article intends to investigate whether there is the possibility of having English as a global language used all over the world with one variety only. One variety of English will reduce the miscommunication among people speaking English. The research was conducted by library research by looking at the requirements of a global language, its spread in the world, and the related problems. The results show that English has fulfilled the requirements of a global language looking from its history and the spread of its speakers. However, it has a lot of varieties in either English speaking countries or in the developing countries where English functions as a second and foreign language. The varieties are found not only in the pronunciation, but in the vocabulary and grammar as well. Usually the native languages play an important role in these varieties. All these facts indicate that English might become a global language. However, having one variety of English still needs a long time to go.